Yifei Sanjie Formula Treats Chronic Obstructive Pulmonary Disease by Remodeling Pulmonary Microbiota - Wu, Yueying; Meng, Hui; Qiao, Bo; Li, Ning; Zhang, Qiang; Jia, Wenqing; Xing, Haijing; Li, Yuqing; Yuan, Jiali; Yang, Zhongshan (Frontiers in Medicine, 2022)
Chronic obstructive pulmonary disease (COPD) is one of the most common pulmonary diseases. Evidence suggests that dysbiosis of pulmonary microbiota leads to the COPD pathological process. Yifei Sanjie Formula (YS) is widely used to treat diseases in respiratory systems, yet little is known about its mechanisms. In the present study, we first established the fingerprint of YS as the background for UHPLC-QTOF-MS. Components were detected, including alkaloids, amino acid derivatives, phenylpropanoids, flavonoids, terpenoids, organic acids, phenols, and the like. The therapeutic effect of YS on COPD was evaluated, and the pulmonary function and ventilatory dysfunction (EF50, TV, and MV) were improved after the administration of YS. Further, the influx of lymphocytes was inhibited in pulmonary parenchyma, accompanied by down-regulation of inflammation cytokines via the NLRP3/caspase-1/IL-1β signaling pathway. The severity of pulmonary pathological damage was reversed. Disturbed pulmonary microbiota was discovered to involve an increased relative abundance of Ralstonia and Mycoplasma and a decreased relative abundance of Lactobacillus and Bacteroides in COPD animals. However, the subversive effect was shown. The abundance and diversity of pulmonary microflora were remodeled, especially increasing beneficial genua Lactobacillus and Bacteroides, as well as downregulating pathogenic genua Ralstonia and Mycoplasma in the YS group. Environmental factor correlation analysis showed that growing pulmonary microbiota was positively correlated with the inflammatory factor, referring to Ralstonia and Mycoplasma, as well as negatively correlated with the inflammatory factor, referring to Lactobacillus and Bacteroides. These results suggest that the effects of YS involved remodeling lung microbes and anti-inflammatory signal pathways, revealing that intervention microbiota and an anti-inflammatory may be a potential therapeutic strategy for COPD.